Penerapan Model Pembelajaran Tipe Jigsaw pada Materi “Mekanisme Transport Zat” - Lenny Handayani (Biology Teaching and Learning, 2022)
Abstract. Learning science is often considered as a learning that is boring and difficult to understand, so we need a learning model that can make science lessons fun and easy to understand. The material "Mechanisms of Substance Transport" is one of the biological science materials which is quite difficult to understand, for this reason, a class action research was carried out applying the Jiqsaw type learning model with the aim of making it easier for students to understand the material and improving learning outcomes of the material "Mechanisms of Substance Transport". This research is a class action research using 2 cycles involving students of class XI IPA MAN Insan Cendekia Gorontalo. The results of data analysis using the descriptive method showed that there was an increase in completeness from cycle 1 to cycle 2 of 13.48%, and an increase in the average score from cycle 1 to cycle 2 of 10.73%. The application of the Jiqsaw type learning model in this study can improve the learning outcomes of the material "Substance Transport Mechanisms", as evidenced by an increase in student completeness and an increase in the average score from cycle 1 to cycle 2.Keywords : Jiqsaw, substance transport mechanism